Restauração de lesões cervicais livres de cárie com resina composta bulk fill – 24 meses, estudo clínico, randomizado e cego - Cavazzini, Andressa Mara (2024)
Objective: to clinically evaluate, for a period of 24 months, restorations of caries-free cervical lesions (LCLC) restored with Bulk Fill composite resin. Materials and Methods: 60 LCLC were selected, divided into two experimental groups: Filtek Z350: control with conventional composite resin and Filtek BF: Bulk Fill composite resin. The restorations were evaluated according to the USPHS criteria – marginal adaptation, anatomical shape, marginal discoloration, caries formation, postoperative sensitivity and retention – in the following periods: initial, 7, 30, 180 and 720 days. The results obtained were subjected to statistical analysis using the Friedman ANOVA test (p < 0.05), followed by the Durbin-Conover post-test (p < 0.05) and Wilcoxon non-parametric intra- group analysis. (p < 0.05) for intergroups. Results: it was possible to observe important differences between the groups, in which the Bulk fill resin presented superior clinical performance in the criteria evaluated regarding marginal adaptation, discoloration of the restorations, anatomical shape and, mainly, dentin sensitivity. Regarding the criteria for caries formation and retention, both groups obtained similar results. Conclusion: Bulk Fill composite resins obtained superiority in USPHS criteria in the treatment of caries-free cervical lesions, proving to be a promising material to be considered in this treatment context.